A RELIGIOUS AND POLITICAL SIGNIFICANCE OF THE FIVE FUNDAMENTAL DEMANDS OF SHAYKH UTHMAN BN FODUYE FROM BAWA JAN-GWARZO - Muhammad Dahiru Shuni; Mukhtar Umar Dagimun (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Shaykh Uthman bn Foduye started his preaching and teaching career at the age of twenty in 1774, moving from one place to another. He however, did not had contact with the kings of the land of Gobir until in about 1780 after attracting a number of substantial followers. Of all the four rulers of Gobir from Sultan Bawa to Yunfa, the relationship between Shaykh and Bawa was the most cordial. Bawa was one of the most powerful rulers of Gobir kingdom. The Shaykh invited him to practice Islam properly and establish justice in his land. Later on, Bawa became doubtful about his friendly attitudes towards the Shaykh. Consequent upon that, he planned against him at his court in Magami on Eid Adha festival but his plan could not be executed. He therefore changed his mind and offered some gifts which the Shaykh refused to take considering it as a bribe. Thus, the Shaykh requested for five things instead which were; to allow him preach in the land, not to stop anybody who wishes to accept Islam, to respect those wearing turban, to free all political prisoners and not to overburden the subjects with heavy taxes. This paper examines the religious and political significance of these requests in the light of the Shaykhs relationship with the four rulers of Gobir kingdom from Sultan Bawa to Yunfa. It also analyses the relevance of the discussions to the contemporary Muslims. To achieve this, some of the most relevant original historical sources were consulted and relevant data were evaluated. Syekh Utsman bin Foduye memulai karir dakwah dan mengajarnya pada usia dua puluh tahun pada tahun 1774, berpindah dari satu tempat ke tempat lain. Namun, dia tidak memiliki kontak dengan raja-raja negeri Gobir sampai sekitar tahun 1780 setelah menarik sejumlah pengikut yang substansial. Dari keempat penguasa Gobir dari Sultan Bawa sampai Yunfa, hubungan Syekh dan Bawa adalah yang paling mesra. Bawa adalah salah satu penguasa kerajaan Gobir yang paling kuat. Syekh mengundangnya untuk mempraktekkan Islam dengan benar dan menegakkan keadilan di tanahnya. Belakangan, Bawa menjadi ragu dengan sikap ramahnya terhadap Syekh. Akibatnya, dia berencana melawannya di istananya di Magami pada hari raya Idul Adha tetapi rencananya tidak dapat dilaksanakan. Karena itu dia berubah pikiran dan menawarkan beberapa hadiah yang ditolak oleh Syekh karena menganggapnya sebagai suap. Oleh karena itu, Syekh meminta lima hal, yaitu; untuk mengizinkannya berdakwah di negeri ini, tidak menghentikan siapa pun yang ingin masuk Islam, menghormati mereka yang mengenakan sorban, membebaskan semua tahanan politik dan tidak membebani rakyat dengan pajak yang berat. Makalah ini mengkaji signifikansi agama dan politik dari permintaan ini dalam kaitannya dengan hubungan Syekh dengan empat penguasa kerajaan Gobir dari Sultan Bawa hingga Yunfa. Ini juga menganalisis relevansi diskusi dengan Muslim kontemporer. Untuk mencapai hal ini, beberapa sumber sejarah asli yang paling relevan dikonsultasikan dan data yang relevan dievaluasi.